Peningkatan Hasil Belajar Matematika Materi Bilangan Bulat melalui Penerapan Metode Pembelajaran Two Stay Two Stray (TSTS) pada Siswa Kelas VI SDN 1 Tanjung Raya Bandar Lampung Tahun Pelajaran 2022/2023 - Indasari, Indasari (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2022)
Based on the results of the reflection of class VI teachers at SDN 1 Tanjung Raya, teachers more often use the lecture method and assign assignments. Teachers have not used innovative and creative approaches, methods, or learning models. This causes students to be less enthusiastic about learning mathematics because they are only passive learning objects and only do the tasks given by the teacher. To improve this, the Two Stay Two Stray (TSTS) type of cooperative learning model was chosen. This research is a classroom action research which consists of 3 cycles. The research subjects were teachers (researchers) and sixth grade students at SDN 1 Tanjung Raya with a total of 22 students. As an observer, the researcher's colleagues were chosen. The variable of this research is Learning Outcomes. Data were collected with test and non-test techniques. Data analysis used quantitative and qualitative descriptive analysis. The results showed that the application of mathematics learning through the application of the Two Stay Two Stray (TSTS) type cooperative learning model can improve the learning outcomes of sixth grade students at SDN 1 Tanjung Raya. The suggestion from the researcher is that research on the Two Stay Two Stray (TSTS) type of cooperative learning model should not stop here, but can be forwarded to future research in order to obtain more accurate results regarding the Two Stay Two Stray (TSTS) type of cooperative learning model.